Review of the British Thoracic Society Winter Meeting 2012, 5 to 7 December, London, UK. Issue 3 (12th January 2013) - Bayes, Hannah Kelly; Church, Alistair Colin; Fisher, Andrew J; ,
Abstract : This review highlights new developments in scientific and clinical research presented at the British Thoracic Society Winter Scientific Meeting held from 5 to 7 December 2012. Although a wide spectrum of respiratory research was presented at the meeting the content of the review focuses specifically on the key themes of pleural disease, interstitial lung disease and future therapies in respiratory medicine. Advances in clinical and translational respiratory research presented in the major symposia and spoken sessions related to these areas are summarised. Additional sessions covering lifestyle dilemmas in the context of respiratory disease and the early career investigator awards are also highlighted.